Verweer tegen het geweld : een onderzoek van de Quakers naar de oplossing van de internationale conflicten en een gedachtenwisseling daarover. (Amsterdam : Wereldbibliotheek, 1956)
Translation of a 4th writing by the US Quakers (since 1949) with political analysis of the international situation after WWII, militarisation, enemy, image building between East and West. Experiences by the Quakers with nonviolence and an appeal for the introduction of nonviolence in foreign policy relations. Comments by Dwight Macdonald, Norman Thomas, Reinhold Niebuhr, Karl Menninger, George Kennan.